2021
DOI: 10.3904/kjim.2020.116
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of serum uric acid levels and prevalence of hyper- and hypouricemia in a Korean general population of 172,970

Abstract: Background/Aims: We investigated the distribution of serum uric acid (SUA) levels and estimated the prevalence of hyperuricemia and hypouricemia in the Korean population. Methods: This cross-sectional study used data from the Korean Genome and Epidemiology Study and included 172,970 participants (58,981 men and 113,989 women) aged 40 to 79 years. Hypouricemia and hyperuricemia were defined as SUA level ≤ 2.0 mg/dL and > 7 mg/dL, respectively. The prevalence of hyperuricemia and hypouricemia was evaluated by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
2
16
1
1
Order By: Relevance
“…The prevalence of hyperuricemia in the general population of Korea has been reported in different ways. Koo et al [29] reported that the prevalence of hyperuricemia was 133.25 per 1,000 persons in men and 8.17 per 1,000 persons in women (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013). In another study [13], the proportion of hyperuricemia was 11.4% (17.0% in men and 5.9% in women).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hyperuricemia in the general population of Korea has been reported in different ways. Koo et al [29] reported that the prevalence of hyperuricemia was 133.25 per 1,000 persons in men and 8.17 per 1,000 persons in women (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013). In another study [13], the proportion of hyperuricemia was 11.4% (17.0% in men and 5.9% in women).…”
Section: Discussionmentioning
confidence: 99%
“…Serum uric acid levels are different between men and women, and the prevalence of hyperuricemia in adult males is higher than in females 51) . Sex hormones may play a role in regulating the expression or activity of urate transporters because SLC2A9 may have a stronger association with lower serum uric acid levels in females, whereas ABCG2 may have a stronger association with higher serum uric acid levels in males 52) .…”
Section: Regulation Of Urate Transporters In the Gut And Kidneymentioning
confidence: 97%
“…Hypouricemia is frequently defined using an SUA concentration of ≤2.0 mg/dL [ 5 ]. Using this reference value, the prevalence of hypouricemia in the general population was reported for Japan [ 8 , 9 , 10 , 11 ] and Korea [ 12 ]. These two countries have similar prevalences of hypouricemia at between 0.2 and 0.4%.…”
Section: Prevalence Of Hypouricemiamentioning
confidence: 99%